The contribution of Imam Shafi’i and Imam Malik ibn Anas to the field of Islamic law: comparative study - Ahmad Ashimi, Tijani (Fakulti Pengajian Peradaban Islam (FPPI), Universiti Islam Selangor, 2024)
The contribution of Muslim scholars to the field of various knowledge is remarkable. Down the history, early Muslim scholars have contributed immensely to the field of Natural sciences, Social sciences, Human sciences and religious sciences ; perhaps, that is due to the intellectual freedom enjoyed by scholars which motivates them to think critically and creatively, as well as their ability to transform the ideals of the Qur’an to daily conduct such as hard work, Perseverance, sincerity honesty and patience in seeking knowledge for the sake of knowledge. Based on this fact, this conference paper aims to explore some achievements accomplished by some gigantic Muslim scholars ( such as Abu ‘Abdullah Mhuammad ibn Idris , and Abu ‘Abdullah Malik Ibn Anas ibn Malik ) to the field of religious sciences with particular reference to dimension of Islamic Law. Yet, in order to achieve the objectives of this conference paper, historical approach will be applied, that is by conducting historical study of their roots and personalities, followed by their Unique works and intellectual achievement. Lastly, the paper will provide a brief conclusion and the lessons that can be learnt from the accomplishment of these genius Muslim Scholars.